Physical Activity Relationship With Metabolic Syndrome In Adults Age At Work Area of Upt Lambu Health Center Subdistrict Lambu Bima Regency - Saddad Tanrewali, Muhammad (Afiasi : Jurnal Kesehatan Masyarakat, 2019)
Metabolic Syndrome (SM) on a person if found three of five components consisting of blood pressure ≥ 130/85 mmHg or on antihypertensive medication, HDL cholesterol levels <40 mg / dL in men and <50 mg / dL in women, hypertriglyceridemia ≥150 mg / dL, fasting serum glucose levels are high ≥100 mg / dL and random blood glucose ≥200 mg / dL and central obesity (abdominal circumference ≥90 cm in men and women ≥80 cm). The purpose of this study to analyze factors associated with the incidence of metabolic syndrome in adult age at UPT Lambu health center working area Lambu subdistrict Bima regency. This type of research is observational analytic with cross sectional study. The samples studied are mostly drawn from the population of young adults (18-40 years) and middle age (41-60 years), which amounted to 145 people. Bivariate analysis using chi-square test. The results showed that there was a relationship with the incidence of metabolic syndrome physical activity with p-value = 0.006, p <α of 0.05 means that there is a relationship between lifestyles with the incidence of metabolic syndrome. The need for the role of health workers to always educate the public about the importance of health and prevention of disease especially need to do a degenerative disease in order to improve public health adequately. The need for community empowerment in improving early warning against non-communicable disease risk factors, either against themselves, family and community environment. For example, by forming Posbindu PTM (Pos Integrated Development of Non-Communicable Diseases).